Optimisasi Biaya Distribusi Furniture dengan Metode Tocm-Sum Approach dan Lowest Supply Lowest Cost - Elpita Sari Hasibuan; Rina Filia Sari (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
PT. Jipta Rimba Djaja is a company engaged in the manufacture of furniture, one of which is the manufacture of plywood. The key to the success of a company can be determined from how the company's marketing, so as to get maximum profit. In order to achieve this goal, the program that must be carried out for the company is to distribute goods or services produced to consumers. In solving transportation problems, there are two solutions, namely the initial solution and the optimal solution. Initial settlement is a solution to find an allocation of goods/products from one source to several destinations. There are many methods that can be used to determine the initial solution, including the Lowest Supply Lowest Cost (LSLC) method and the Total Oppurtunity Cost Matrix-SUM (TOCM-SUM) Approach method. Which is used to determine the most effective allocation of goods and aims to find out the results of optimizing transportation costs from sources to certain destinations with the minimum possible cost. Based on calculations using the TOCM-SUM APPROACH method and the Lowest Supply Lowest Cost (LSLC) method on the transportation costs of distributing furniture (plywood) at PT. Tjipta Rimba Djaja in January 2023 of Rp. 2,507,898,000, - and in February 2023 the optimal cost of distribution is the same, namely Rp. 1,457,324,000. Where the difference between the two is that the calculation steps of the Lowest Supply Lowest Cost (LSLC) method are not as many as those of the TOCM-SUM APPROACH method. So that the completion is faster than the TOCM-SUM APPROACH method.